Chimaerocyon gen. nov., a morphologically aberrant myrmecophilous genus of water scavenger beetle (Coleoptera: Hydrophilidae: Sphaeridiinae) - Fikáček, Martin; Maruyama, Munetoshi; Vondráček, Dominik; Short, Andrew E.z. (Zootaxa, 2013)
A new hydrophilid genus Chimaerocyon gen. nov. containing two species, C. shimadai sp. nov. (Malaysia: Pahang) and C. sumatranus sp. nov. (Indonesia: Sumatra), is described. Specimens of C. shimadai were collected from brood cells in a nest of Pheidole singaporensis Özdikmen, 2010. The biology of C. sumatranus remains unknown. A molecular phylogeny based on four genes (cox1, cox2, 18S and 28S) supports the placement of the genus as deeply nested within the Cercyon-group of the tribe Megasternini. This position is supported by the subdistal position of the median spur in the hind wing (unique to Megasternini) and the presence of sucking disc on male maxilla (unique for Megasternini+Sphaeridiini). The remaining external morphology differs substantially from other representatives of Megasternini. The hypothesis that the aberrant morphology of Chimaerocyon gen. nov. is a consequence of myrmecophily is discussed.